Pengembangan Wisata Budaya Di Kecamatan Baktiraja Kabupaten Humbang Hasundutan - Torus Manusun Sianturi; Hidayat Amsasi; Robert Sibarani (Universitas Negeri Medan, 2021)
This research aims to identify, describe and find out the impact of the development of cultural tourism on the community in Marbun Toruan Village, Baktiraja District, Humbang Hasundutan Regency. The problem focuse on the potential of cultural tourism in the village of Marbun Toruan and its development in order to approach this problem requires a theoretical reference from some previous researchers. The method used is descriptive qualitative. Data is collected through interviews, observations, questionnaires and documentation. This study conclude that the Baktiraja district which has the potential for cultural tourism such as Tombak Sulu Sulu, Sisingamangaraja Palace, Batu Si siungkap ungkapon, Aek Sipangolu, Hariara Tungkot, Batu Hundul. The Humbang Hasundutan Regency Government gives responsibility to the Department of Transportation and Tourism to develop the tourism potential in tourist attraction of Baktiraja. This tourism object does not receive serious attention to be developed as a tourist destination so it is not inferior to other tourist destinations in North Sumatra that have been developed.